Rural Decentralization In Burkina Faso : Local Level Institutions and Poverty Eradication - Donnelly-Roark, Paula (World Bank, Washington, DC, 2012)
The note focuses on the leading role of local level institutions (LLIs) in Burkina Faso, in rural decentralization, and poverty eradication, to enhance equitable prosperity. It is based on the study undertaken by the National Decentralization Commission in Burkina Faso, which draws on case studies in Sanmatenga, Sissili, Houet, and Yatenga, and, presents sociological evidence that certain high-performing LLIs contribute to equitable economic development. Economic findings support this, showing that both lower inequality levels, and lower poverty levels, are linked to a high degree of internal village organization. Contextually, LLIs surround, connect, and manage communities, incorporating many different kinds of indigenous organizations, and functions. Three categories of institutions active at the local level are identified: value institutions, which focus on activating, and maintaining the stability of local governance, and values of the society; production institutions, focused on accessing resources from the national government, so as to increase productivity; and, service-asset management institutions, which integrate productivity, and growth values, focused on managing, and expanding local assets for sustainable development. External aid will need to map these LLIs to guide pro-poor investment, and financing of community driven development, and encourage local governments to formalize participation.